2019
DOI: 10.1039/c8dt04728f
|View full text |Cite
|
Sign up to set email alerts
|

Acetate as a model for aspartate-based CXCR4 chemokine receptor binding of cobalt and nickel complexes of cross-bridged tetraazamacrocycles

Abstract: Ni and Co complexes of cross-bridged vs. unbridged tetraazamacrocycle acetate complexes reveal preferences likely to impact CXCR4 antagonist interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Numerous studies 5,6 have demonstrated that the first-row transition metal complexes of these ethylene cross-bridged tetraazamacrocycles are among the most kinetically stable towards harsh acidic/basic conditions of known synthetic transition metal complexes. Yet, their tetradentate nature ensures labile coordination sites that allow reactivity and/or binding ability that has made these complexes favoured for catalytic, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] biomedical imaging, [22][23][24][25][26][27][28][29][30] and inorganic drug compound [31][32][33][34][35] applications.…”
mentioning
confidence: 99%
“…Numerous studies 5,6 have demonstrated that the first-row transition metal complexes of these ethylene cross-bridged tetraazamacrocycles are among the most kinetically stable towards harsh acidic/basic conditions of known synthetic transition metal complexes. Yet, their tetradentate nature ensures labile coordination sites that allow reactivity and/or binding ability that has made these complexes favoured for catalytic, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] biomedical imaging, [22][23][24][25][26][27][28][29][30] and inorganic drug compound [31][32][33][34][35] applications.…”
mentioning
confidence: 99%
“…Cross-bridged tetraazamacrocycles that have an additional two-carbon bridge between non-adjacent nitrogen atoms of a tetraazamacrocycle, which are particularly rigid and lead to very kinetically stable metal complexes, have been extensively studied by Weisman [ 1 , 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], Springborg [ 13 , 14 , 15 ], Hubin [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ], Archibald [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ], Tripier [ 31 , 32 , 33 , 34 , 35 , 36 ], and others [ 37 , 38 , 39 ]. This stability conferred on these transition metal complexes shows great promise in such applications as homogeneous catalysis [ 40 , 41 , 42 , 43 ], inorganic drug candidates [ 20 , 24 , 26 , 27 , 44 , 45 , 46 ], and biomedical imaging agents [ ...…”
Section: Introductionmentioning
confidence: 99%
“…1 above. 8–12 These are desirable traits for restricting the complex coordination geometry 13–18 and for applications where the kinetic stability of the complex is desirable, such as in biological or medical uses, 19–29 or in catalytic reactions under harsh conditions. 30–42 Recently, we have decided to investigate ethylene cross-bridged analogues of the larger pentaazamacrocycles, hoping to produce similarly useful, kinetically stable coordination complexes.…”
Section: Introductionmentioning
confidence: 99%